The Complete Story of the Galveston Horror. - 20160731 frey50 (United Pub. of Amer. usa, 1900)
Incidents of the awful tornado, flood and cyclone disaster, personal experiences of survivors, horrible looting of dead bodies and the robbing of empty homes, pestilence from so many decaying bodies unburied, barge captains compelled by armed men to tow dead bodies to sea, millions of dollars raised to aid the suffering survivors, President McKinley orders army rations and army tents issued to survivors and orders US troops to protect the people and property, tales of the survivors from galveston, adrift all night on rafts, acts ofvalor, United States soldiers drowned, great herosim, great vandalism, great horror, a second johnstown flood, but worse; hundreds of men, women and children drowned, no way of excape, only death! death! Everywhere!
Written by the survivors